Gender Inequality in The Labour Market in Kazakhstan And Uzbekistan - Krystyna GOMÓŁKA (Communications of International Proceedings, 2024)
The aim of the following article is to present gender inequality in the labour market in Kazakhstan and Uzbekistan. Gender inequality was researched by analyzing documents providing rights for women and men in Kazakhstan and Uzbekistan. The author presented the unequal treatment of women in the labour market by examining the causes of the level of employment of women and men - contract workers, higher unemployment among women, and finally by the lower remuneration offered to women workers in both countries. The research was conducted on the basis of the analysis of statistical data available on the websites of the Kazakh and Uzbek statistical offices.
Keywords: Gender inequality; labour market; Kazakhstan; Uzbekistan; employment; unemployment; wages